Monetary Policy Transmission and Inflation Dynamics in Indonesia: Evidence from BI7DRR, Money Supply, Exchange Rate, and Structural Breaks - Vera Lutfiyah; Marseto Marseto (Journal of Business, Social and Technology, 2026)
Background: Several monetary policy instruments can influence inflation; however, in the case of Indonesia, the transmission of these policies is highly dependent on external shocks, such as wars and oil price fluctuations. Objective: The purpose of this study is to investigate the monetary policy transmission mechanism affecting inflation in Indonesia using the BI 7-Day Reverse Repo Rate (BI7DRR), money supply (M2), exchange rate, and structural breaks over the period 2019–2024. Methods: This study employs monthly time-series data from January 2019 to December 2024, along with Ordinary Least Squares (OLS) regression, the Augmented Dickey–Fuller (ADF) unit root test, classical assumption tests, and the Bai–Perron multiple structural break test. Results: The results indicate that BI7DRR, M2, and the exchange rate jointly affect inflation in Indonesia. The ADF test confirms that all variables are stationary at the first difference level, while the Bai–Perron test detects multiple structural breaks around 2020 and 2022, which were largely associated with the emergence of COVID-19 and global monetary tightening, respectively. Conclusion: The conclusion drawn from this study essentially reflects a time-structural model of how monetary policy transmission affects inflation dynamics in Indonesia. Maintaining price stability requires adaptive monetary policy, exchange rate stabilization, and fiscal–monetary coordination.